Evaluation of respiratory symptoms and spirometric indices in Ghaemshahr,s textile workers - O Aminian; SAR Mozaffari; SA Sharifian; M Rokni; F Ahmadzadeh; H Heidariam Miri (طب کار)
Abstract Background: Workers who exposed to cotton dust are at risk of some occupational lung diseases such as byssinosis and chronic bronchitis. In general respiratory symptoms like chronic cough, sputum and dyspnea are more common in cotton dust exposed workers. With continuous exposure, progression of disease and pulmonary dysfunction will happen. In this study, we assessed the effect of cotton dust exposure on pulmonary function. Methods: In this survey, 141 textile workers who exposed to cotton dust have been elected as exposed group and data was gathered by ATS,s standard questionnaire, physical exam and spirometry. Spirometric indices such as FVC, FEV1, FEV1/FVC, FEF25-75% and PEFR were measured. Results: Outcomes show that some respiratory symptoms such as cough, sputum and episodic productive cough (chronic bronchitis) have significant increase in cotton dust exposed group and decreased mean of FVC, FEV1, and FEV1/FVC percentage have been seen. These results suggest high prevalence of obstructive airway disease in this group. Conclusion: According to results in our study textile workers are at risk of progression of respiratory symptoms and decreased of pulmonary function. Physical exam and spirometry can detect the disease at early stage.